2013
DOI: 10.5194/cp-9-1519-2013
|View full text |Cite
|
Sign up to set email alerts
|

Can an Earth System Model simulate better climate change at mid-Holocene than an AOGCM? A comparison study of MIROC-ESM and MIROC3

Abstract: The importance of evaluating models through paleoclimate simulations is becoming more recognized in efforts to improve climate projection. To evaluate an integrated Earth System Model, MIROC-ESM, we performed simulations in time-slice experiments for the mid-Holocene (6000 yr before present, 6 ka) and preindustrial (1850 AD, 0 ka) periods under the protocol of the Coupled Model Intercomparison Project 5/Paleoclimate Modelling Intercomparison Project 3. We first give an overview of the simulated global climates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…7). This is a region where previous analyses have shown that simulated changes in monsoon rainfall reflect the competition between enhanced contrast in moist static energy between land and ocean and increased local evaporation over the warmer oceans (Ohgaito et al, 2013). Ensemble mean changes in the North American Monsoon System, and the Southern Hemisphere monsoons are also small ( Fig.…”
Section: Monsoonal Responsementioning
confidence: 81%
“…7). This is a region where previous analyses have shown that simulated changes in monsoon rainfall reflect the competition between enhanced contrast in moist static energy between land and ocean and increased local evaporation over the warmer oceans (Ohgaito et al, 2013). Ensemble mean changes in the North American Monsoon System, and the Southern Hemisphere monsoons are also small ( Fig.…”
Section: Monsoonal Responsementioning
confidence: 81%
“…The explicit simulation of these components of the climate system greatly facilitates comparisons with natural records (e.g. Wasson and Claussen, ; Ohgaito et al ., ).…”
Section: Model Evaluation and Benchmarkingmentioning
confidence: 97%
“…In particular, nutrients in 110 the upper ocean are sustained by upwelling from the deeper ocean and nutrient inputs from external sources. Some studies suggest that nutrient availability to marine ecosystems could decline in the future through reduction of nutrient upwelling because of intensified stratification (e.g., Ono et al, 2008;Whitney et al, 2013;Yasunaka et al, 2016). Conversely, other https://doi.org/10.5194/gmd-2019-275 Preprint.…”
Section: Target 65mentioning
confidence: 99%
“…For land, the Minimal Advanced Treatments of 195 Surface Interaction and Runoff (MATSIRO) model (Takata et al, 2003) is coupled to simulate the atmosphere-land boundary conditions and freshwater input into the ocean. Considering the application possibility of the ESM to long-term climate simulations of more than hundreds of years, e.g., paleoclimate studies (Ohgaito et al, 2013;Yamamoto et al, 2019), the horizontal resolution of the atmosphere is set to have T42 spectral truncation, which is approximately 2.8° intervals for latitude and longitude. The vertical resolution is 40 layers up to 3 hPa with a hybrid σ-p coordinate, as in 200 MIROC5.…”
Section: Model Configurationsmentioning
confidence: 99%